2002
DOI: 10.1046/j.1365-2109.2002.00683.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between dietary lipid:protein ratios and plasma growth and thyroid hormone levels in juvenile Arctic charr, Salvelinus alpinus (Linnaeus)

Abstract: Sexually immature Arctic charr, Salvelinus alpinus (Linnaeus), were fed one of five isoenergetic practical diets of differing lipid:protein ratios (0.98, 0.67, 0.41, 0.26, 0.19) for an 84-day period to examine the influence of diet composition on growth, and growth hormone (GH) and thyroid hormone physiology. All five diets supported growth at approximately the same rate, but the diet with a lipid: protein ratio of 0.98 had the lowest weight gain and highest food conversion ratios. A GH enzymelinked immunosorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…Furthermore, the observed plasma GH changes may be in response to the E 2 -induced elevation in plasma total lipid concentrations. This argument is supported by evidence of elevated plasma GH levels in fish fed high lipid diets (Martí-Palanca et al, 1996;Company et al, 1999;Pérez-Sánchez, 2000;Cameron et al, 2001), and the observed influence of ration levels on plasma GH concentrations in fishes (Farbridge et al, 1992). Such a response would be found equally in in vivo and in vitro models, since even in the in vitro model, the donor fish were E 2 -primed before the pituitary glands were harvested.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, the observed plasma GH changes may be in response to the E 2 -induced elevation in plasma total lipid concentrations. This argument is supported by evidence of elevated plasma GH levels in fish fed high lipid diets (Martí-Palanca et al, 1996;Company et al, 1999;Pérez-Sánchez, 2000;Cameron et al, 2001), and the observed influence of ration levels on plasma GH concentrations in fishes (Farbridge et al, 1992). Such a response would be found equally in in vivo and in vitro models, since even in the in vitro model, the donor fish were E 2 -primed before the pituitary glands were harvested.…”
Section: Discussionmentioning
confidence: 90%
“…Significantly increased GH amounts were detected in gilthead sea bream fed low protein diets however this was unlikely to be translated into enhanced growth since reduced hepatic GH binding and IGF-1 amounts were also found in gilthead sea bream fed low protein diets (Pérez-Sánchez et al 1995). In addition a diet high in lipid composition has been shown to increase plasma GH levels for rainbow trout (Holloway and Leatherland 1998;Holloway et al 1999), Arctic Charr (Cameron et al 2002) and gilthead sea bream (Martí-Palanca et al 1996;Company et al 1999;Pérez-Sánchez 2000). Two explanations currently exist for elevated plasma GH levels when fish are fed diets high in lipid content.…”
Section: Nutritional Stressmentioning
confidence: 87%
“…This effect is attributed to reduced feedback inhibition by IGF‐I associated with mobilization of lipid reserves (Björnsson, 1997). In Arctic charr, however, plasma lipids may stimulate GH directly, resulting in higher plasma GH in Arctic charr fed high lipid diets than in Arctic charr fed low lipid diets (Cameron et al ., 2002). It is thus possible that the higher plasma GH of the fed fish in the present study may be a response to increased concentration of plasma or tissue lipids derived from the feed.…”
Section: Discussionmentioning
confidence: 99%